Is There a Problem in the Laboratory? - Wendt, Alexander Nicolai (Frontiers in Psychology, 2018)
Problem-solving research in the field of psychology has been closely linked to laboratory investigations throughout its development. However, there is a questionable conceptual assumption underlying this commitment to the laboratory, namely the assumption that one can reduce all problem-solving behavior to a cognitive mechanism. Upon validating this assumption from a phenomenological standpoint, doubts about its foundations emerge. For when we consider the experiential conditions that characterize a problematic situation, we come to determine several phenomenal aspects that are not taken into account in this approach. A phenomenologically revised notion of the problem therefore demands a modification of the scope of the empirical research. First, this paper investigates the configuration of the laboratory as an arena of experience based on Lewin’s field theory. This investigation indicates instructions as a key component of the laboratory. Second, a phenomenological description proposes a novel understanding of the problem. In this part it is shown that it is wrong to presume that problematic situations can be evoked arbitrarily by instructions. Finally, further contemplations help outlining the empirical requirements for exhaustive research. They call for novel paradigms in empirical psychology, such as live streaming, which are more faithful to the phenomenology of problems.